Combined use of heat pipe, thermoelectric generator, and hybrid nano-enhanced cooling channels for performance improvement of PV module and estimations by using radial basis network - Selimefendigil, Fatih; Okulu, Damla; Öztop, Hakan Fehmi (Springer, 2025)
In this study, 3D computational studies of photovoltaic (PV) module with different cooling methods are considered. For cooling and thermal management of PV panels, PV+channel, PV+heat pipe (HP), PV+thermoelectric generator (TEG), and PV+HP+TEG systems are integrated. In the case of channel cooling, ternary hybrid nanofluid (THNF) with different loading is used. The TEG device's cold side temperature ranges from 10oC\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ 10\,<^>{{\text{o}}} {\text{C}} $$\end{document} to 25oC\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ 25\,<^>{{\text{o}}} {\text{C}} $$\end{document}. PV cell temperature decreases by roughly 1o\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$1<^>\text {o}$$\end{document}C when TEG is used and its cold side temperature is lowered. Cooling channel with THNF is very effective when fluid temperature is low. At Re=10, using THNF as the cooling medium instead of base fluid results in a 7oC\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ 7\,<^>{{\text{o}}} {\text{C}} $$\end{document} reduction in the average PV-cell temperature while with an increase in nanoparticle loading in the base fluid, the average cell temperature drops about linearly. With additional cooling channels, lower PV-cell temperatures may be attained while increasing the number of cooling channels from N=2-N=10 led to temperature drops of 40.6oC\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ 40.6\,<^>{{\text{o}}} {\text{C}} $$\end{document} and 37.4oC\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$ 37.4\,<^>{{\text{o}}} {\text{C}} $$\end{document}, respectively. The channel cooling system provides the lowest PV-cell temperature at the lowest value of Tin\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$T_{{{\text{in}}}}$$\end{document}, followed by the HP cooling, TEG+HP cooling, and TEG system. At the lowest Tin\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$T_{{{\text{in}}}}$$\end{document} value, channel cooling, PV+TEG+HP, and PV+TEG have respective efficiency values of 15. 2%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$15.2\%$$\end{document}, 14.85%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$14.85\%$$\end{document}, and 14.8%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$14.8\%$$\end{document}, while at the highest Tin\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$T_{{{\text{in}}}}$$\end{document} value, 14.3%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$14.3\%$$\end{document}, 14.85%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$14.85\%$$\end{document}, and 13.9%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$13.9\%$$\end{document}. A hybrid computational method with radial basis network is proposed. As compared to high fidelity parametric study, computation time drops by a factor of 1/25, while it accurately captures the temperature variation of cell and power production of TEG. The outcomes are useful for the development of experimental and computational methods related to thermal regulation of PV modules and integrated systems.
Keywords: Channel cooling; Heat pipe; Thermoelectric; PV module; Finite element method; Radial basis network